X 4 2x 3 3x 2 4x 1
![x 4 2x 3 3x 2 4x 1](https://media.cheggcdn.com/study/a64/a64f42cc-b3d7-4ce8-b51d-803f289c784c/image.jpg)
- X 4 2x 3 3x 2 4x 1 0
- X 4 2x 3 3x 2 4x 6 )/( x 2 2x 1
- X 5 3x 4 4x 3 2x 2 12x 16
- P x )= 1 2x 2 3x 4x 3 6x 4 1
- 5x 3 x 2x 2 4 )+( 3x 2 1 4x
- The equation x 4 2x 3 3x 2 4x 1 0
- X 4 2x 3 4x 2 3x 10 0
- Cho a x )= 2x 4 4x 3 3x 2 4x 1
- X 4 2x 3 3x 2 4x 6 divided by x 2 2x 1
- F x )= 3x 4 2x 3 37x 2 24x 12
- If f x )= x 4 4x 3 3x 2 2x 1
- (- 4x 2 x 12 )+( 2x 3 3x 2 4
- X 3 3x 2 2x 1 )/( x 2 4x 4 dx dx dy
- 3x 4 2x 3 4x 2 10 12 dibagi x 2
- P x )= 6x 4 2x 4x 3 3x 2 10 x 3 3x